1996
DOI: 10.1128/mcb.16.6.2878
|View full text |Cite
|
Sign up to set email alerts
|

Either of the Major H2A Genes but Not an Evolutionarily Conserved H2A.F/Z Variant of Tetrahymena thermophila Can Function as the Sole H2A Gene in the Yeast Saccharomyces cerevisiae

Abstract: H2A.F/Z histones are conserved variants that diverged from major H2A proteins early in evolution, suggesting they perform an important function distinct from major H2A proteins. Antisera specific for hv1, the H2A.F/Z variant of the ciliated protozoan Tetrahymena thermophila, cross-react with proteins from Saccharomyces cerevisiae. However, no H2A.F/Z variant has been reported in this budding yeast species. We sought to distinguish among three explanations for these observations: (i) that S. cerevisiae has an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…These differences could reflect neutral mutations that do not cause functional distinctions between the two. This hypothesis is supported by the fact that either of the T. thermophila major H2A genes can function as the sole H2A gene in yeasts and each confers a similar coldsensitive phenotype (22). However, sequence comparisons indicate that the H2A1 or H2A2 proteins of T. thermophila and T. pyriformis are virtually identical between the two species whereas H2A1 and H2A2 within each species retain the divergent C-terminal ends (24).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These differences could reflect neutral mutations that do not cause functional distinctions between the two. This hypothesis is supported by the fact that either of the T. thermophila major H2A genes can function as the sole H2A gene in yeasts and each confers a similar coldsensitive phenotype (22). However, sequence comparisons indicate that the H2A1 or H2A2 proteins of T. thermophila and T. pyriformis are virtually identical between the two species whereas H2A1 and H2A2 within each species retain the divergent C-terminal ends (24).…”
Section: Discussionmentioning
confidence: 78%
“…Because the yeast Saccharomyces cerevisiae is unusual among eukaryotes in that it does not seem to have a minor H2A variant (22), it was not possible to test this hypothesis by gene knockout experiments in that organism. Functional analysis of the H2A.F/Z variant in the fission yeast Schizosaccharomyces pombe by gene knockout indicated that the gene was not essential but did affect growth and chromosome segregation (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the notable exception of Saccharomyces cerevisiae (Liu et al, 1996), H2A.F/Z variants have been identified in a number of highly evolutionarily distant organisms. The reported characterization of the Arabidopsis cH2AvAt cDNA demonstrates that H2A.F/Z histone variants have been conserved in plants and are highly homologous to their animal and lower eukaryote counterparts, indicating that these proteins evolved under similar strong selection pressure.…”
Section: H2af/z Histone Variantmentioning
confidence: 99%
“…It has been proposed that H2A.F/Z variants could modify chromatin structure and in some way control the transcriptional competence of chromatin in response to extracellular signals and during development (Stargell et al, 1993;Liu et al, 1996).…”
Section: H2af/z Histone Variantmentioning
confidence: 99%